2018
DOI: 10.1177/1352458518763094
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine signaling in multiple sclerosis: Lost in translation

Abstract: Multiple sclerosis (MS) is a common neurological disorder of putative autoimmune origin. Clinical studies delineate abnormal expression of specific cytokines over the course of disease. Preclinical studies using animal models of MS have yielded promising results in manipulating the activity of certain cytokines to improve the clinical outcome. However, the translation of these findings into the clinic is often disappointing. The reason for this might be the complex nature of cytokine networks and the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 58 publications
1
73
0
Order By: Relevance
“…Neuroinflammation is thought to play a role in many neuropsychiatric and neurological conditions [1][2][3][4]; however, its exact contribution remains poorly understood [5][6][7]. This is partially due to limited diagnostic tools to measure inflammation in the central nervous system (CNS) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroinflammation is thought to play a role in many neuropsychiatric and neurological conditions [1][2][3][4]; however, its exact contribution remains poorly understood [5][6][7]. This is partially due to limited diagnostic tools to measure inflammation in the central nervous system (CNS) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed soluble mediators of inflammation released by activated lymphocytes and resident immune cells represent key regulators of the auto-immune response in MS. Specific proinflammatory molecules, including interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor (TNF), and interferon-gamma, promote immune cell infiltration through the blood-brain barrier, leading to demyelination and axonal damage (Göbel et al, 2018). In addition, experimental studies showed that proinflammatory molecules also alter neuronal functioning by promoting excitotoxic neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…These virulent factors hence trigger both the cellular and humoral immune responses [11,12,13]. Accordingly, cytokines responses have been found to play crucial role in the pathogenesis of most bacterial infection [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Cytokines as immunological mediators are involved in the immune build up in inflammatory conditions of the udder [18,19]. They are known for their cell signalling roles and anti-inflammatory pathways during infection as they strike a balance between the cellular and humoral immunity [20,21,17]. An experimental study following S. aureus intramammary challenge in lactating cows indicated that IL-12 is a good marker in response to S. aureus challenge and vaccination [22].…”
Section: Introductionmentioning
confidence: 99%